2022
DOI: 10.1057/s41599-022-01239-9
|View full text |Cite
|
Sign up to set email alerts
|

Race- and gender-based under-representation of creative contributors: art, fashion, film, and music

Abstract: Motivated by the well-established benefits to society of artistic creation and of demographic diversity, we investigate the gender and racial/ethnic composition of influential contributors to four creative domains. Women make up 51% of the U.S. population but are underrepresented at influential levels of contemporary art (28%), high fashion (45%), box office film (27%), and popular music (17%). Marginalized racial/ethnic groups make up 39% of the U.S. population yet comprise approximately half that figure in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…We hypothesized that individuals with marginalized gender identities (including women, nonbinary, gender nonconforming, trans, and people of multiple sexes/genders) would face barriers to participation in plant science and that these would compound with socioeconomic disadvantages and/or historical oppression to further limit participation by intersectional individuals. We cannot test this hypothesis directly without knowing the gender identities of the authors in the paper, so we aimed to instead measure perceptive discrimination based on sexism that disadvantages individuals with names normatively associated with femininity (NNFs) ( 41 , 42 ). To test this prediction, names of corresponding authors for each paper were isolated and classified as either 1) names normatively associated with masculinity (NNMs) or 2) names normatively associated with femininity (NNFs) and used as a proxy for gender.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that individuals with marginalized gender identities (including women, nonbinary, gender nonconforming, trans, and people of multiple sexes/genders) would face barriers to participation in plant science and that these would compound with socioeconomic disadvantages and/or historical oppression to further limit participation by intersectional individuals. We cannot test this hypothesis directly without knowing the gender identities of the authors in the paper, so we aimed to instead measure perceptive discrimination based on sexism that disadvantages individuals with names normatively associated with femininity (NNFs) ( 41 , 42 ). To test this prediction, names of corresponding authors for each paper were isolated and classified as either 1) names normatively associated with masculinity (NNMs) or 2) names normatively associated with femininity (NNFs) and used as a proxy for gender.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that individuals with marginalized gender identities (including women, non-binary, gender non-conforming, trans, and people of multiple sexes/genders) would face barriers to participation in plant science and that these would compound with socioeconomic disadvantages and/or historical oppression to further limit participation by intersectional individuals. We cannot test this hypothesis directly without knowing the gender identities of the authors in the paper, so we aimed to instead measure perceptive discrimination based on sexism, that disadvantages individuals with names normatively associated with femininity (Topaz et al 2022; Maril & Gill 2018). To test this prediction, names of corresponding authors for each paper were classified as either 1) names normatively associated with masculinity (NNMs) or 2) names normatively associated with femininity (NNFs) and used as a proxy for gender.…”
Section: Resultsmentioning
confidence: 99%
“…New technologies and expanding infrastructure have opened the door for cutting-edge research to be conducted at monumental scales. Despite this noteworthy growth, access to resources is not evenly distributed across the globe and recent studies have revealed striking participation gaps and longstanding disparities tied to colonialism, economic inequality, and systemic biases (Amarante et al 2021; Maas et al 2021; Marks et al 2021; Trisos et al 2021; Ebenezer et al 2022; Topaz et al 2022; Wapman et al 2022). Plant science, in particular, suffers from more acute historical exclusion and ongoing underrepresentation of marginalized identities compared to other biological disciplines (Madzima and MacIntosh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The people already marginalised by society will be most impacted by this loss of income. Further, work opportunities in technology companies can be even more heavily skewed against gender and racial minorities than the creative industries [154,170], meaning profits may be moving from female creatives of colour and into the pockets of white men running tech companies. Furthermore, we wish to acknowledge the effects of job displacement on image subjects.…”
Section: Socio-legal Interventionsmentioning
confidence: 99%